PENGARUH BEBAN KERJA DAN PENERAPAN E-PERFORMANCE TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI : (Studi Kasus Pada PT The Lorry Online Indonesia) - Annisa Maulinda, (2022)
This study is a quantitative study that aims to determine whether there is an influence between workload and implementation of e-performance with job satisfaction as a mediaton variable on employees of PT The Lorry Online Indonesia. The study used 67 respondents with a saturated sampling technique. The analytical technique applied in this research is descriptive analysis technique and inferential analysis through SmartPLS 3.0. Hypothesis testing obtains (1) workload has a positive and significant effect on employee performance. (2) implementation of e-performance has a positive and significant effect on employee performance. (3) workload has a positive and insignificant effect on employee performance which is mediated by job satisfaction. (4) implementation of e-performance has a positive and significant effect on employee performance which is mediated by job satisfaction. (5) job satisfaction has a positive and significant effect on employee performance.